Melambyrsus hoplita Breddin rediscovered (Hemiptera: Pentatomidae: Discocephalinae): redescription of genus and species - Campos, Luiz Alexandre; Roell, Talita (Zootaxa, 2017)
The monotypic Melambyrsus Breddin was described as related to Ochlerus Spinola and Melanodermus Stål, but its identity remained uncertain since the holotype had been considered probably lost. We located in the Senckenberg Deutsches Entomologisches Institut at Müncheberg a female that we believe is the type specimen of Melambyrsus hoplita Breddin, and concluded that both the species and the genus were valid based on somatic and genital characteristics. Here Melambyrsus and its type species M. hoplita are redescribed.